2006
DOI: 10.1177/021849230601400312
|View full text |Cite
|
Sign up to set email alerts
|

Off-Pump Coronary Endarterectomy in High-Risk Patients

Abstract: The outcome of off-pump endarterectomy in patients with diffuse coronary artery disease and increased risk factors for cardiopulmonary bypass was reviewed. Thirty-eight procedures were carried out in 32 patients (21 men and 11 women) aged 59 to 78 years (mean, 69 years). Mean left ventricular ejection fraction was 38.6% (range, 24% - 55%). The number of grafts per patient was 2.6. The left internal mammary artery was used in 29 patients (91%). Endarterectomy was performed on the right coronary artery and its b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Nurozler et al [8] retrospectively studied 32 patients undergoing OPCAB-CE with moderate ventricular impairment (ejection fraction (EF) 38.6%). The mean number of CEs performed per patient was 1.18 ± 0.2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurozler et al [8] retrospectively studied 32 patients undergoing OPCAB-CE with moderate ventricular impairment (ejection fraction (EF) 38.6%). The mean number of CEs performed per patient was 1.18 ± 0.2.…”
Section: Resultsmentioning
confidence: 99%
“…Among these best evidence series, the overall incidence of postoperative MI was 6.1% (11/180). Increased incidence of postoperative MI was particularly notable in patients undergoing multiple endarterectomies [3,6], RCA endarterectomy [8] and endarterectomy performed using a closed approach [6,8]. Notably, however, MI rates were comparable between OPCAB and ONCAB techniques [5,7].…”
Section: Clinical Bottom Linementioning
confidence: 99%
“…Vohra et al 28 reported 4.3% for the postoperative MI rate. Nurozler et al 31 reported a perioperative MI rate of 6.2%. In both of these studies, off-pump technique was used for CE and the majority had single vessel CE to RCA.…”
Section: Discussionmentioning
confidence: 98%
“…The majority (65%) of patients in our study had on-pump CABG, although we feel that CE is easier to perform off-pump, as reported by Vohra and colleagues; 9 however, the results were similar in off-pump and on-pump cases. Nurozler and colleagues 13 reported a perioperative MI rate of 6.2% and overall mortality of 3.1% at 14 AE 3.3 months. In both these studies, off-pump CE was mostly to the right coronary artery only.…”
Section: Discussionmentioning
confidence: 98%